Analysis of Education for Children with Special Needs at Bina Anggita Special School for Autism, Magelang City - Rahmanto, Maulana Irfan; Nurhajimah, Fitri; Wijayanti, Apsari; Fitria, Savira Ananda; Wardana, Aditia Eska (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Education of children with special needs needs to be applied to children who have brain and nervous disorders such as autism, deafness, mental retardation, physical disability, etc. With this review, we must know how to deal with habituation, development and handling of children with special needs. The purpose of this study was to explore information regarding the habituation, development and handling of children with special needs at the Bina Anggita Autism Special School, Magelang City. This research was conducted using a qualitative method with a descriptive approach. This research was conducted by means of in-depth interviews with 1 class teacher and direct observations related to the instruments studied. The data obtained are based on empirical studies conducted by the author. Based on the research that has been done, in general, the education of children with special needs at the Autism Special School of Bina Anggita is carried out practically and theoretically. Theoretically, it is done by integrating the subjects with the one on one method (one teacher one child) using the lecture method. Meanwhile, practically it is done through positive habits. Supporting factors such as books, pictures, and learning tools. Evaluation of the education of children with special needs at the Bina Anggita Autism Special School is implemented by carrying out assessments for children with special needs, namely by carrying out mid tests, PAS, and daily assessments that are carried out directly. Apart from that, there are also extracurricular and co-curricular activities as a supporter of Education for Children with Special Needs at Bina Anggita Autism Special School.